Alexithymia, emotion dysregulation, impulsivity and aggression: A multiple mediation model. (30th March 2016) - Velotti, Patrizia; Garofalo, Carlo; Petrocchi, Chiara; Cavallo, Francesca; Popolo, Raffaele; Dimaggio, Giancarlo
Abstract: There is a need to better understand the antecedent of aggressive behaviors in order to tailor treatments and reduce the associated damage to the others and the self. Possible mechanisms underlying aggression are poor emotional awareness and emotion dysregulation, as well as impulsivity. Here, we examined the relationships among alexithymia, emotion dysregulation, impulsivity and aggression, comparing a mixed psychiatric sample ( N =257) and a community sample ( N =617). The clinical sample reported greater levels of alexithymia, emotion dysregulation, trait impulsivity and aggression, than the community sample. Furthermore, in the community sample, emotion dysregulation and impulsivity mediated the relationship (i.e., accounted for the shared variance) between alexithymia and aggression. In the clinical sample, only emotion dysregulation explained the alexithymia-aggression link. In particular, specific dimensions of the emotion dysregulation (i.e., Negative Urgency) and impulsivity constructs (i.e., cognitive and motor impulsivity) played a unique role in explaining these associations. Finally, controlling for depressive symptoms reduced some of the findings involving impulsivity to nonsignificant results. Overall, our findings add to the extant literature attesting to the relevance of alexithymia and emotion dysregulation for understanding aggression, and providing concrete recommendation for the treatment and prevention of aggressive tendencies. Highlights: We examined the relation between alexithymia and aggression. Psychiatric patients reported deficits in emotion regulation and alexithymia. Psychiatric patients reported greater levels of impulsivity and aggression. Emotion dysregulation mediated the effect of alexithymia on aggression. Also impulsivity mediated such relation in a community sample.